Whole-genome selective scans detect genes associated with important phenotypic traits in goat (Capra hircus) - Wan, Xing; Jing, Jia-Nan; Wang, Dong-Feng; Lv, Feng-Hua (Frontiers in Genetics, 2023)
Goats with diverse phenotypic traits play an important role in animal husbandry. However, the genetic mechanisms underlying some complex production traits remain unclear in goats. In this study, we focused on the worldwide goat breeds and used whole-genome resequencing data in 361 samples from 68 breeds to detect genomic selection sweep regions associated with important agronomic traits. We identified 210 - 531 genomic regions for six phenotypic traits. Further gene annotation analysis revealed 332, 203, 164, 300, 205, and 145 candidate genes for dairy, wool, prolificacy, horned/polled, ear size, and white coat color traits. In addition to some of these genes reported previously (e.g., KIT, KITLG, NBEA, RELL1, AHCY, and EDNRA), we also discovered novel genes, such as STIM1, NRXN1, and LEP, associated with traits such as polled and big ear size. Overall, our study detected a set of new genetic markers for genetic improvement in goats and provided novel insights into the genetic mechanisms of complex traits in goats and related farm animals.